The effect of Magic Box Play Therapy (Mystery Box) on the Laguage Development of Children Aged 4-5 tahun - Sensussiana, Titis; Listiyanawati, Mutiara Dewi; Vioneery, Deoni (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: The golden age stage of children is at the age of 5 years. One of the games that can stimulate language skill’s children's development is playing magic box. Playing with this magic box play therapy can stimulate other aspects of development.Objective: The purpose of this study was to determine the effect of magic box games on the language development of children aged 4-5 years at KB-TK Taruna Prima.Methods: This research method uses quantitative methods with pre-experiment with one group pre and post test design. Total population 53 students with total sampling. Play activities are carried out twice a week fo1 1 week.Results: The result of this study is that magic box play therapy is effective on the language development of children aged 4-5 years at KB-TK Taruna Prima, as evidenced by statistical tests showing p value <0.000.Conclusion: Teacher can do magic box play therapy to stimulate child development. Educational institutions develop media to stimulate child development with magic box play therapy.